Method for preparing cellulose-based porous microspheres by doping nanoparticles and application of cellulose-based porous microspheres

The carbon nanotube metal nanoparticles were prepared by ultrasonic stirring of carbon oxide nanotubes and metal salt solution, and added them to the cellulose solution for emulsification. The cellulose-based porous microspheres were prepared by reverse suspension method, which solved the problems of complex preparation, long production cycle and poor antibacterial effect in the prior art, and achieved simple and easy large-scale production and excellent antibacterial performance.

CN120137245APending Publication Date: 2025-06-13SAIPU (HANGZHOU) FILTRATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510224175.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The existing cellulose microsphere preparation methods are complex, have long production cycles, high equipment costs, are not suitable for large-scale production, and have poor antibacterial effects.

Method used

Carbon nanotubes were prepared by ultrasonic stirring of carbon oxide nanotubes and metal salt solution, and then added to the cellulose solution. After emulsification treatment, cellulose-based porous microspheres were prepared by reverse suspension method.

Benefits of technology

The prepared cellulose-based porous microspheres have a simple and easy preparation process, are suitable for large-scale production, and show excellent antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137245A_ABST
    Figure CN120137245A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing cellulose-based porous microspheres by doping nanoparticles, which comprises the following steps: adding a metal salt solution into an oxidized carbon nanotube dispersion liquid, stirring, and carrying out post-treatment I to obtain carbon nanotube metal nanoparticles; the preparation method comprises the following steps: adding carbon nanotube metal nanoparticles into a pre-prepared cellulose solution, and uniformly mixing to obtain a composite system solution; adding the obtained composite system liquid into an immiscible oil phase system, emulsifying to prepare a suspension taking an oil phase as a continuous phase, curing the suspension, and performing post-treatment II to obtain the cellulose microspheres. Compared with a polymer film, the porous cellulose microspheres have a higher specific surface area and can provide more binding sites. The cellulose / carbon nano tube / (copper, zinc and silver) porous composite microspheres prepared by the method have excellent antibacterial performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cellulose microspheres, and particularly relates to a method for preparing cellulose-based porous microspheres doped with nanoparticles and applications thereof. Background Art

[0002] Since the 21st century, due to the gradual depletion of petroleum resources and the fact that most of them are non-degradable, causing irreversible damage to the ecological environment, renewable resources have become a new research hotspot. Cellulose is the most abundant natural polysaccharide in nature and is one of the best substitutes for petroleum derivatives. Cellulose microspheres have the characteristics of strong renewability, stable chemical properties, easy separation and recovery, large specific surface area, good hydrophilicity, etc., and are widely used in materials, chemical engineering, biology, medicine and other fields.

[0003] As a new type of one-dimensional nanomaterial, multi-walled carbon nanotubes (CNTs) have the following advantages when applied to the biomedical field: First, CNTs have excellent mechanical properties and can effectively improve the compressive properties of the matrix material; second, the large specific surface area and excellent electrical conductivity of CNTs are more conducive to the adsorption of biomolecules such as proteins; third, after CNTs are introduced into the matrix material as a reinforcing material, the material can obtain a nano-network structure and appropriate porosity, providing more binding sites for nanoparticles and being more conducive to mass exchange.

[0004] Due to its large specific surface area, nano-copper has a good adsorption effect and has a good killing effect on fungi, so it is widely used in the fields of antibacterial and deodorization. Nano-silver is an excellent broad-spectrum bactericide and has a strong inhibitory and killing effect on dozens of pathogenic microorganisms such as Neisseria gonorrhoeae, Escherichia coli, and Chlamydia trachomatis. At the same time, nano-silver can kill hundreds of bacteria in a short time and does not produce drug resistance. Nano-zinc has strong bactericidal properties against Gram-positive bacteria and has been widely used in the field of anti-mildew. Abdul Wahab Jatoi et al. (Cellulose acetate / multi-wall carbon nanotube / Ag nanofiber composite for antibacterial applications, Materials Science and Engineering: C, Volume 110, 2020, 110679) reported a cellulose acetate / carbon nanotube / silver nanoparticle (CA / CNTs / Ag) nanofiber composite based on antibacterial applications. This literature prepared cellulose acetate nanofibers loaded with silver nanoparticles by electrospinning. The silver nanoparticles were anchored on carbon nanotubes (CNTs) and embedded in the cellulose acetate (CA) matrix, so it had good antibacterial properties. However, due to the complex electrospinning process, long production cycle, and high equipment cost, it is not conducive to large-scale production. Summary of the Invention

[0005] Aiming at the deficiencies of the above-mentioned technologies, the purpose of the present invention is to provide a method for preparing cellulose-based porous microspheres doped with nanoparticles. This method is simple and easy to implement, and the prepared cellulose microspheres have good antibacterial effects.

[0006] The present invention also provides a cellulose-based porous microsphere prepared by the above preparation method.

[0007] The present invention further provides an application of the above cellulose-based porous microspheres as an antibacterial agent.

[0008] To achieve the above technical objectives, the present invention is realized through the following technical solutions:

[0009] A method for preparing cellulose-based porous microspheres doped with nanoparticles, comprising: adding carbon nanotubes oxidized with acid to a metal salt solution, ultrasonically stirring, and performing post-treatment I to obtain carbon nanotube metal nanoparticles; adding the carbon nanotube metal nanoparticles to a pre-prepared cellulose solution, and mixing evenly to obtain a composite system liquid; adding the obtained composite system liquid to an immiscible oil-phase emulsion system, emulsifying to prepare a suspension with the oil phase as the continuous phase and the composite system liquid as the dispersed phase, performing solidification treatment on the dispersed phase in the suspension, and performing post-treatment II to obtain cellulose-based porous microspheres.

[0010] Preferably, the metal salt is at least one of copper sulfate, zinc sulfate, silver sulfate, copper chloride, zinc chloride, silver chloride, copper nitrate, zinc nitrate, and silver nitrate. The metal salt solution is generally an aqueous solution of the metal salt. The concentration of the aqueous solution of the metal salt is 0.1-0.5 mol / L.

[0011] Preferably, the carbon nanotubes oxidized with acid can be commercially available products or can be prepared by oneself. When prepared by oneself, a mixture of sulfuric acid and nitric acid can be selected to oxidize the carbon nanotubes:

[0012] (i) Disperse 0.1-1.0 g of CNTs in 100 mL of sulfuric acid and nitric acid (3:1; v / v),

[0013] ultrasonically treat in an ultrasonic bath at 50-70 °C for 2-4 h;

[0014] (ii) Obtain oxidized CNTs by centrifuging at 4000 rpm for 15-25 min, and then dry in an oven at 50-70 °C for 10-15 h.

[0015] Preferably, the (oxidized) carbon nanotubes are multi-walled (oxidized) carbon nanotubes or single-walled (oxidized) carbon nanotubes; more preferably, the (oxidized) carbon nanotubes are multi-walled (oxidized) carbon nanotubes.

[0016] Preferably, after adding carbon nanotubes to the metal salt solution, stir for 2 to 5 h; then perform post-treatment I. The post-treatment I is: centrifugally separate to obtain metal nanoparticles (CNTs / (Cu 2+ , Zn 2+ , Ag + ) nanoparticles), then dry in an oven at 40 to 60 °C for 10 to 15 h, and finally perform heat treatment at 250 to 350 °C for 2 to 5 h to obtain the carbon nanotube metal nanoparticles. Such as (RC / CNTs / Cu), (RC / CNTs / Zn), and (RC / CNTs / Ag).

[0017] Preferably, the mass ratio of the metal salt to the carbon nanotubes is 1 mol:(4 to 40) g. As a further preference, the mass ratio of the metal salt to the carbon nanotubes is 1 mol:(10 to 20) g; as a specific preference, the mass ratio of the metal salt to the carbon nanotubes is 1 mol:

[0018] (10 to 15) g.

[0019] Preferably, the cellulose used is natural cellulose, and the preparation method of the cellulose solution is as follows: put the cellulose into the pre-cooled sodium hydroxide-urea aqueous solution, stir at 350 to 450 r / min for 5 to 15 min, and then centrifuge at 2800 to 5000 r / min for 10 to 20 min for degassing at room temperature. After centrifugation, place the cellulose solution in an ice-water bath for use. The pre-cooled sodium hydroxide-urea aqueous solution is prepared by the following method: weigh a certain amount of sodium hydroxide, urea, and water (mass ratio of 5 to 8:10 to 14:78 to 82), mix them evenly, and then put them into the refrigerator and pre-cool to -18 to 10 °C.

[0020] Preferably, the concentration of cellulose in the cellulose solution is 2 to 10%; more preferably 3 to 8%, and even more preferably 3 to 5%. As a specific embodiment, the mass ratio of the cellulose to the pre-cooled sodium hydroxide-urea aqueous solution is 4:96.

[0021] Of course, the present invention can also use other celluloses other than natural cellulose. When using other types of celluloses, corresponding dissolution methods can be selected, and the purpose is to obtain a homogeneous cellulose solution.

[0022] Under stirring conditions, carbon nanotube metal nanoparticles (CNTs / metal nanocomposites) are added to the cellulose solution, and the solution is ultrasonically treated for 0.5 to 2 hours to obtain a cellulose-carbon nanotube-metal ion composite system liquid. Preferably, the weight percentage of carbon nanotube metal nanoparticles in the composite system liquid is 3 to 15%. Preferably, the mass ratio of carbon nanotube metal nanoparticles to cellulose in the composite system liquid is 1:(1 to 2); more preferably 1:(1.1 to 1.5); even more preferably 1:(1.2 to 1.5).

[0023] Preferably, the obtained composite system liquid is added to an immiscible oil phase system, and stirred and emulsified at a stirring speed of 500 to 2000 r / min and at room temperature for 3 to 6 h to obtain the suspension with the oil phase as the continuous phase and the composite system liquid as the dispersed phase.

[0024] Preferably, the oil phase emulsion system is composed of an emulsifier and an oil phase; wherein the oil phase is selected from one or more of vegetable oil, liquid paraffin, xylene (o-xylene, m-xylene, etc.); the emulsifier is selected from one or more of Span60, Span80, Span80, Tween80.

[0025] Preferably, the volume ratio of the emulsifier to the oil phase in the oil phase emulsion system is (1 to 5):100, preferably (2 to 4):100; the volume ratio of the composite system liquid to the oil phase system is 1:(3 to 4.5); further 1:(3.5 to 4.5).

[0026] As a specific preferred scheme, Span80 (or other emulsifier) is dissolved in liquid paraffin (or other oil phase) and stirred at a speed of 500 to 2000 r / min for 10 to 60 min, and then a certain amount of the above composite system liquid is added within 0.5 to 2 h (preferably 1 h), and the obtained suspension is stirred and emulsified at a stirring speed of 500 to 2000 r / min and at room temperature for 3 to 6 h.

[0027] Preferably, the pH value of the suspension is adjusted to neutral with dilute hydrochloric acid (for example, the pH value is adjusted to 7.0 by dropping 10% dilute hydrochloric acid, and the suspension solidifies to form regenerated cellulose microspheres), to achieve the solidification or ethanol is added to achieve solidification; the post-treatment II is: the solidified system is allowed to stand and layered, the oil phase is washed with water and then recycled; the cellulose microspheres separated from the aqueous phase are washed to obtain the final cellulose microspheres. Taking liquid paraffin as an example, after standing, the mixture system is divided into two layers: the upper layer is the liquid paraffin organic phase which can be recycled by washing with water, and the lower aqueous phase is rinsed with distilled water multiple times and then washed with acetone several times to obtain regenerated cellulose microspheres, labeled as RC / CNTs / (Cu, Zn, Ag).

[0028] The microsphere sample finally prepared by the present invention can be stored by cooling and drying or stored in a 20% ethanol solution at 0-5°C.

[0029] As a specific implementation, a method for preparing cellulose microspheres includes the following steps:

[0030] (1) Synthesis of carbon nanotube / (copper, zinc, silver) nanocomposite

[0031] 1. Oxidize carbon nanotubes with a mixture of sulfuric acid and nitric acid: Disperse 0.1-1.0 g of CNTs in 100 mL of sulfuric acid and nitric acid (3:1; v / v), and ultrasonically treat in an ultrasonic bath at 50-70°C for 2-4 h;

[0032] 2. Centrifuge the oxidized CNTs at 4000 rpm for 15-25 min using ethanol and deionized water respectively, and then dry in an oven at 50-70°C for 10-15 h;

[0033] 3. Prepare 100 mL of 0.25 M metal ion solution, and then stir the solution on a magnetic stirrer for 2-5 h.

[0034] 4. Then, add 0.1-1.0 g of oxidized CNTs to the metal ion solution, and ultrasonically treat at 40-60°C for 1-3 h to uniformly disperse the CNTs to obtain a dispersion.

[0035] 5. Obtain CNTs / metal nanoparticles by centrifugation, and dry in an oven at 40-60°C for 10-15 h.

[0036] 6. Generate metal nanoparticles and perform heat treatment at 250-350°C for 2-5 h.

[0037] (2) Preparation of cellulose solution

[0038] 7. Weigh a certain amount of sodium hydroxide, urea, and water (mass ratio 5-8:10-14:78-82), mix them evenly, and pre-cool in a refrigerator to -18-10°C.

[0039] 8. Quickly put the cellulose sample into the pre-cooled solution, stir at 350-450 r / min for 5-15 min, and then centrifuge at 2800-5000 r / min for 10-20 min for degassing at room temperature. After centrifugation, place the cellulose solution in an ice-water bath.

[0040] (3) Preparation of cellulose / carbon nanotube / (copper, zinc, silver) nanocomposite

[0041] 9. Add CNTs metal nanocomposites, such as (RC / CNTs / Cu), (RC / CNTs / Zn), or (RC / CNTs / Ag), to the cellulose solution under stirring conditions. Ultrasonically treat the solution for 0.5 - 2 hours;

[0042] 10. Dissolve 2.7% Span80 in liquid paraffin and stir at a speed of 500 - 2000 r / min for 10 - 60 min. Then, add a certain amount of the above cellulose solution within 1 h. The resulting suspension is stirred and emulsified at a stirring speed of 500 - 2000 r / min and at room temperature for 3 - 6 h.

[0043] 11. Under the above conditions, add 10% dilute hydrochloric acid dropwise to adjust the pH to 7.0. The suspension solidifies to form regenerated cellulose microspheres. Let it stand, and the mixture system is divided into two layers: the upper layer is the liquid paraffin organic phase, which can be recycled by washing with water, and the lower aqueous phase is washed with distilled water multiple times and then washed with acetone 3 times to obtain the regenerated cellulose microspheres, labeled as (RC / CNTs / Cu), (RC / CNTs / Zn), or (RC / CNTs / Ag).

[0044] 12. Store these microsphere samples by freeze-drying or store them in a 20% ethanol solution at 0 - 5 °C.

[0045] A cellulose-based porous microsphere is prepared by the method for preparing a cellulose-based porous microsphere doped with nanoparticles described in any of the above technical solutions.

[0046] Another object of the present invention is to provide the application of the described cellulose-based porous microspheres in the antibacterial field.

[0047] The present invention utilizes the oxidized carbon nanotubes to fully adsorb copper, zinc, and silver ions, and prepares carbon nanotube / metal nanocomposites by reducing copper, zinc, and silver ions. It dissolves cellulose in an alkali / urea system at low temperature, disperses the carbon nanotube / metal nanocomposites into the cellulose solution by ultrasonic treatment, and finally prepares cellulose / carbon nanotube / metal porous composite microspheres by the reverse suspension method. The cellulose / carbon nanotube / (copper, zinc, silver) porous composite microspheres prepared by the present invention have excellent antibacterial properties.

[0048] Compared with modified celluloses such as cellulose acetate, the regenerated cellulose used in the present invention is made from natural plant fibers, is biodegradable, does not contain harmful chemicals, and does not irritate the skin. It is an environmentally friendly material with excellent properties. At the same time, the cellulose-based porous microspheres provided by the present invention can load a variety of metal nanoparticles, providing a better solution for different bacterial species in the antibacterial field.

[0049] The beneficial effects of the present invention are:

[0050] The porous cellulose microspheres loaded with copper nanoparticles anchored on multi-walled carbon nanotubes CNTs / (copper, zinc, silver) were prepared by the reverse suspension method. Due to their excellent thermal, electrical, and mechanical properties, multi-walled carbon nanotubes (CNTs) provide an effective medium for fixing copper, zinc, and silver nanoparticles. Nano-copper, nano-zinc, and nano-silver have excellent bactericidal effects in the antibacterial field and have beneficial effects on biological cells. Using the porous cellulose microspheres as a carrier improves the biocompatibility, biodegradability, hydrophilicity, and moisture retention of the polymer microspheres. Compared with polymer films, the porous cellulose microspheres have a higher specific surface area and can provide more binding sites. The cellulose / carbon nanotube / (copper, zinc, silver) porous composite microspheres prepared in this invention have excellent antibacterial properties. Description of the Drawings

[0051] Figure 1 is the flow chart of the preparation method of the cellulose / carbon nanotube / (copper, zinc, silver) porous composite microspheres.

[0052] Figure 2 is the scanning electron microscope image of the cellulose / carbon nanotube / copper porous composite microspheres.

[0053] Figure 3 is the bar chart of the antibacterial rate of the cellulose / carbon nanotube / (copper, zinc, silver) porous composite microspheres. Detailed Embodiments

[0054] As Figure 1 shown below, the following specific examples are used to further illustrate the method described in this invention, but do not limit this invention.

[0055] In the examples, in vitro antibacterial experiments were used to evaluate the antibacterial properties of the prepared cellulose-based porous microspheres. The antibacterial rate R was calculated according to formula (1), and the formula is as follows:

[0056]

[0057] In the formula: R - antibacterial rate, %

[0058] N 0 - average number of colonies in the culture medium of the blank control group (cfu / mL)

[0059] N - average number of colonies in the culture medium of the experimental group (cfu / mL)

[0060] The specific steps are as follows:

[0061] 1. Test strains:

[0062] The standard strains of Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus (Gram-positive bacteria) were selected as the test strains.

[0063] 2. Operating steps:

[0064] (1) Sterilize all experimental utensils and prepared culture media by autoclaving before the test, and conduct all experimental operations in a sterile room.

[0065] (2) Preparation of bacterial suspension: Use a sterile inoculation loop to pick bacteria from the slant twice, streak inoculate in a nutrient agar plate, and place it in a constant temperature incubator at 37°C for 24 h. Prepare 50 mL of buffer solution in a conical flask, use a sterile inoculation loop to pick the actively growing secondary-passage bacteria on the culture dish and inoculate them into 50 mL of buffer solution, shake well, and place it in the incubator for 24 h. Prepare a bacterial suspension, apply quantitative bacterial suspensions with different dilution concentrations on nutrient agar plates, culture for 24 h and then count. Take the bacterial suspension with a concentration of 1×10 5 cfu / mL as the experimental solution.

[0066] (3) Add 2 mL of the above-mentioned bacterial suspension to a conical flask containing 48 mL of phosphate buffer solution, then add a quantitative test sample, seal it, and place it in a shaking incubator at 37°C for 24 h. Set the shaking speed of the shaker to 150 r / min.

[0067] (4) Use a pipette to suck 0.1 mL of the cultured bacterial liquid from different samples and spread it on nutrient agar plates. Inoculate 3 plates in parallel for each sample. After covering and sealing the plates, invert them in a constant temperature incubator at 37°C for 24 h and then count.

[0068] (5) After the test, sterilize all utensils and waste involved in the experiment by autoclaving before further disposal.

[0069] Example 1

[0070] Disperse 0.5 g of CNTs (purchased from Aladdin) in 100 mL of sulfuric acid and nitric acid (3:1; v / v), and ultrasonically treat it in an ultrasonic bath at 60°C for 3 h; centrifuge and wash at 4000 rpm for 20 min to obtain oxidized CNTs, and then dry them in an oven at 60°C for 12 h to obtain oxidized CNTs.

[0071] Prepare 100 mL of 0.25 M CuSO 4 solution, and then stir the solution on a magnetic stirrer for 3 hours. Then, add 0.3 g of oxidized CNTs to the CuSO 4 solution, and ultrasonically treat it at 50°C for 1 h to uniformly disperse the oxidized CNTs. Obtain CNTs / Cu 2+ nanoparticles by centrifugation, and dry them in an oven at 50°C for 12 h. Generate copper nanoparticles, and conduct heat treatment at 300°C for 2 h to obtain CNTs / Cu nanoparticles.

[0072] Weigh a certain amount of sodium hydroxide, urea, and water (mass ratio of 7:12:81), mix them evenly, and place them in a refrigerator to pre-cool to -12°C. Quickly put the cellulose (bagasse, industrial grade) sample into the pre-cooled solution (cellulose mass fraction is 4wt%), stir at 400 r / min for 10 min, and then centrifuge at 4000 r / min for 15 min to degas at room temperature. After centrifugation, place the cellulose solution in an ice-water bath. Under stirring conditions, add 3wt% of CNTs / Cu nanoparticles to the cellulose solution (i.e., the cellulose solution accounts for 97wt% and the CNTs / Cu nanoparticles account for 3wt%). Ultrasonically treat the solution for 1 hour to obtain the RC / CNTs / Cu composite system liquid; dissolve 2.7% (volume ratio) Span80 in liquid paraffin (200 mL), stir at a speed of 1000 r / min for 30 min, and then add a certain amount of the above RC / CNTs / Cu composite system liquid (water-oil volume ratio is 1:4) within 1 hour. The resulting suspension is stirred and emulsified at a stirring speed of 1000 r / min and room temperature for 5 hours. Under the above conditions, add 10% dilute hydrochloric acid dropwise to adjust the pH value to 7.0, and the suspension solidifies to form regenerated cellulose microspheres. Let it stand, and the mixture system is divided into two layers: the upper layer is the liquid paraffin organic phase, which can be recycled by washing with water, and the lower aqueous phase is washed with distilled water multiple times and then washed with acetone 3 times to obtain regenerated cellulose microspheres, labeled as RC / CNTs / Cu; these microsphere samples can be stored by cooling and drying or stored in a 20% ethanol solution at 0 - 5°C when not in use. Finally, RC / CNTs / Cu porous cellulose microspheres are obtained, and the scanning electron micrograph is as Figure 2 shown.

[0073] Detect the inhibitory effects of this example on Escherichia coli and Staphylococcus aureus: Take 2 mL of the suspension of each of the two bacteria with a concentration of 1×10 5 cfu / mL as the experimental liquid. Add the above-mentioned bacterial suspensions to conical flasks containing 48 mL of 0.9% sodium chloride buffer solution respectively, then add 1 g of the RC / CNTs / Cu porous cellulose microsphere sample, seal it, and place it in a 37°C culture shaker for 24 h. The shaker speed is set at 150 r / min. Use a pipette to suck 0.1 mL of the cultured bacterial liquid from the sample and spread it on a nutrient agar plate. Take three plates for parallel inoculation. After covering and sealing the plates, invert them in a 37°C constant temperature incubator for 24 h and then count. The test results show that the antibacterial rate of the RC / CNTs / Cu porous cellulose microspheres against Escherichia coli is 92.85%, and the antibacterial rate against Staphylococcus aureus is 87.81%.

[0074] Example 2

[0075] According to a method similar to Example 1, 0.5 g of CNTs (purchased from Aladdin) was dispersed in 100 mL of sulfuric acid and nitric acid (3:1; v / v), and ultrasonic treatment was carried out in an ultrasonic bath at 60 °C for 3 h; centrifugal cleaning was carried out at 4000 rpm for 20 min to obtain oxidized CNTs, and then dried in an oven at 60 °C for 12 h to obtain oxidized CNTs;

[0076] Prepare 100 mL of 0.25 M ZnCl 2 solution, and then stir the solution on a magnetic stirrer for 3 hours. After that, 0.3 g of oxidized CNTs was added to the ZnCl 2 solution, and ultrasonic treatment was carried out at 50 °C for 1 h to uniformly disperse the oxidized CNTs. CNTs / Zn 2+ nanoparticles were obtained by centrifugation and dried in an oven at 50 °C for 12 h. Zinc nanoparticles were generated and heat-treated at 300 °C for 2 h to obtain CNTs / Zn nanoparticles. Weigh a certain amount of sodium hydroxide, urea, and water (mass ratio 7:12:81), mix them evenly, and pre-cool them in a refrigerator to -12 °C. Quickly put the cellulose (bagasse, industrial grade) sample into the pre-cooled solution (cellulose mass fraction 4 wt%), stir at 400 r / min for 10 min, and then centrifuge and degas at 4000 r / min for 15 min at room temperature. After centrifugation, place the cellulose solution in an ice-water bath.

[0077] Under stirring conditions, 3 wt% of CNTs / Zn nanoparticles were added to the cellulose solution. The solution was ultrasonically treated for 1 hour to obtain an RC / CNTs / Zn composite system solution; 2.7% Span80 was dissolved in liquid paraffin (200 mL) and stirred at 1000 r / min for 30 min, and then a certain amount of the above-obtained RC / CNTs / Zn composite system solution (water-oil volume ratio 1:4) was added within 1 h. The resulting suspension was stirred and emulsified at a stirring speed of 1000 r / min and room temperature for 5 h. Under the above conditions, 10% dilute hydrochloric acid was added dropwise to adjust the pH value to 7.0, and the suspension solidified to form regenerated cellulose microspheres. After standing, the mixture system was divided into two layers: the upper layer was the liquid paraffin organic phase, which could be recycled by washing with water, and the lower layer aqueous phase was rinsed with distilled water multiple times and then washed with acetone 3 times to obtain regenerated cellulose microspheres, labeled as RC / CNTs / Cu; these microsphere samples can be stored by cooling and drying or stored in a 20% ethanol solution at 0 - 5 °C when not in use. Finally, RC / CNTs / Zn porous cellulose microspheres were obtained.

[0078] Detect the inhibitory effects of this example on Escherichia coli and Staphylococcus aureus: Take 2 mL of a concentration of 1×10 5Two bacterial suspensions with a concentration of cfu / mL were used as experimental solutions. The above-mentioned bacterial suspensions were respectively added to conical flasks containing 48 mL of 0.9% sodium chloride buffer solution, and then 1 g of RC / CNTs / Zn porous cellulose microsphere samples were added and sealed. They were placed in a 37°C culture shaker and cultured for 24 h. The shaker speed was set at 150 r / min. 0.1 mL of the cultured bacterial solution was pipetted from the sample and spread on a nutrient agar plate. Three plates were taken for parallel inoculation. After covering and sealing the plates, they were inverted and placed in a 37°C constant temperature incubator for 24 h and then counted. The test results showed that the antibacterial rate of RC / CNTs / Zn porous cellulose microspheres against Escherichia coli was 94.78%, and the antibacterial rate against Staphylococcus aureus was 80.43%.

[0079] Example 3

[0080] Disperse 0.5 g of CNTs (purchased from Aladdin) in 100 mL of sulfuric acid and nitric acid (3:1; v / v), and ultrasonically treat it in an ultrasonic bath at 60°C for 3 h; centrifuge and wash it at 4000 rpm for 20 min to obtain oxidized CNTs, and then dry them in a drying oven at 60°C for 12 h to obtain oxidized CNTs;

[0081] Prepare 100 mL of 0.25 M AgNO 3 solution, and then stir the solution on a magnetic stirrer for 3 hours. Then, add 0.3 g of oxidized CNTs to the AgNO 3 solution, and ultrasonically treat it at 50°C for 1 h to uniformly disperse the oxidized CNTs. Obtain CNTs / Ag + nanoparticles by centrifugation, and dry them in an oven at 50°C for 12 h. Generate silver nanoparticles and perform heat treatment at 300°C for 2 h to obtain CNTs / Ag nanoparticles. Weigh a certain amount of sodium hydroxide, urea, and water (mass ratio 7:12:81), mix them evenly, and pre-cool them in a refrigerator to -12°C. Quickly put the cellulose (bagasse, industrial grade) sample into the pre-cooled solution (cellulose mass fraction is 4 wt%), stir at 400 r / min for 10 min, and then centrifuge and degas at 4000 r / min for 15 min at room temperature. After centrifugation, place the cellulose solution in an ice-water bath.

[0082] Under stirring conditions, 3 wt% CNTs / Ag nanoparticles were added to the cellulose solution. The solution was ultrasonically treated for 1 hour to obtain an RC / CNTs / Ag composite system solution; 2.7% Span80 was dissolved in liquid paraffin and stirred at a speed of 1000 r / min for 30 min, and then a certain amount of the above composite system solution (water-oil volume ratio of 1:4) was added within 1 h. The resulting suspension was stirred and emulsified at a stirring speed of 1000 r / min and room temperature for 5 h. Under the above conditions, 10% dilute hydrochloric acid was added dropwise to adjust the pH to 7.0, and the suspension was solidified to form regenerated cellulose microspheres. After standing, the mixture system was divided into two layers: the upper layer was the liquid paraffin organic phase, which could be recovered by washing with water, and the lower aqueous phase was washed with distilled water multiple times and then washed with acetone three times to obtain regenerated cellulose microspheres, labeled as RC / CNTs / Cu; these microsphere samples could be stored by freeze-drying or stored in a 20% ethanol solution at 0 - 5 °C when not in use. Finally, RC / CNTs / Ag porous cellulose microspheres were obtained.

[0083] Detect the inhibitory effects of this example on Escherichia coli and Staphylococcus aureus: 2 mL of suspensions of the two bacteria with a concentration of 1×10 5 cfu / mL were taken as the experimental solutions. The above bacterial suspensions were respectively added to conical flasks containing 48 mL of 0.9% sodium chloride buffer solution, and then 1 g of the RC / CNTs / Ag porous cellulose microsphere sample was added and sealed. It was placed in a 37 °C culture shaker and cultured for 24 h. The shaker speed was set at 150 r / min. 0.1 mL of the cultured bacterial liquid was pipetted from the sample and spread on a nutrient agar plate. Three plates were taken for parallel inoculation. After covering and sealing the plates, they were inverted and placed in a 37 °C constant temperature incubator for 24 h and then counted. The test results showed that the antibacterial rate of the RC / CNTs / Ag porous cellulose microspheres against Escherichia coli was 98.76%, and the antibacterial rate against Staphylococcus aureus was 98.43%.

[0084] The column chart of the antibacterial rates of the cellulose / carbon nanotube / (copper, zinc, silver) porous composite microspheres prepared in Examples 1 - 3 is shown in Figure 3 the figure. The antibacterial rates against Escherichia coli and Staphylococcus aureus are both relatively high, especially the antibacterial rate of the cellulose / carbon nanotube / silver porous composite microspheres is the best.

Claims

1. A method for preparing cellulose-based porous microspheres by doping nanoparticles, characterized in that: include: adding oxidized carbon nanotubes to a metal salt solution, stirring with ultrasound, and post-treating the solution to obtain carbon nanotube metal nanoparticles; The carbon nanotube metal nanoparticles are added to the pre-prepared cellulose solution, and the mixture is evenly mixed to obtain a composite system liquid; the obtained composite system liquid is added to an immiscible oil phase emulsification system, and emulsification is performed to prepare a suspension with the oil phase as a continuous phase and the composite system liquid as a dispersed phase, and the dispersed phase in the suspension is solidified, and post-processed to obtain cellulose-based porous microspheres.

2. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The metal salt is at least one of copper sulfate, zinc sulfate, silver sulfate, copper chloride, zinc chloride, silver chloride, copper nitrate, zinc nitrate and silver nitrate.

3. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The mass ratio of the metal salt to the oxidized carbon nanotubes is 1 mol: (4-40) g; the post-treatment I is: centrifugal separation to obtain metal nanoparticles, followed by drying in an oven at 40-60° C. for 10-15 hours, and finally heat treatment at 250-350° C. for 2-5 hours to obtain the carbon nanotube metal nanoparticles.

4. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The weight percentage of the carbon nanotube metal nanoparticles in the composite system liquid is 2-15%; the mass ratio of the carbon nanotube metal nanoparticles to the cellulose in the composite system liquid is 1:1-2.

5. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The oil phase emulsification system consists of an emulsifier and an oil phase; the oil phase is selected from one or more of vegetable oil, liquid paraffin, and xylene; the emulsifier is selected from one or more of Span60, Span80, Span80, and Tween80.

6. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 5, characterized in that: The volume ratio of the emulsifier to the oil phase in the oil phase emulsification system is 1-5:100; the volume ratio of the composite system liquid to the oil phase emulsification system is 1:3-4.

5.

7. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The pH value of the suspension is adjusted to neutral by using dilute hydrochloric acid or ethanol is added to achieve the solidification; the post-treatment II is: the solidified system is allowed to stand, separated into layers, and the oil phase is washed with water and then recycled; the cellulose microspheres separated from the water phase are washed to obtain the final cellulose / carbon nanotube / metal porous composite microspheres.

8. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The obtained composite system liquid is added to the immiscible oil phase emulsification system, and stirred and emulsified for 3 to 6 hours at a stirring speed of 500 to 2000 r / min and room temperature to obtain the suspension with the oil phase as the continuous phase and the composite system liquid as the dispersed phase.

9. The method for preparing cellulose-based porous microspheres by doping nanoparticles according to claim 1, characterized in that: The cellulose adopts natural cellulose, and the preparation method of the cellulose solution is as follows: cellulose is placed in a precooled sodium hydroxide urea aqueous solution, stirred at 350-450 r / min for 5-15 minutes, centrifuged at 2800-5000 r / min for 10-20 minutes at room temperature for degassing, and after centrifugation, the cellulose solution is placed in an ice water bath.

10. A cellulose-based porous microsphere, characterized in that: The microspheres are prepared by the method for preparing cellulose-based porous microspheres with doped nanoparticles according to any one of claims 1 to 9.

11. Use of the cellulose-based porous microspheres according to claim 10 in preparing an antibacterial agent.